Allele Frequencies ofF13AOI, FESFPS and vWA STRs in random Dusun population of Malaysia - Mohd Yusmaidie, Aziz (PPSP, Universiti Sains Malaysia, 2007)
Short Tandem Repeats (STRs) loci are characterized by high level of length polymorphism within and among populations. This polymorphism makes it becomes a blue print for forensic purposes. In this study, STR is applied for determining the allele's frequencies in Duson population in Sabah. This is done by using three different STR loci F13AOI, FESFPS and vWA. About 100 buccal swab samples from Dusun population were collected. Each sample was separated into different envelopes and sealed. Then DNA was extracted from the samples using simple procedure describe by Promega followed by STR typing on the three locus using multiplex kits. Allele frequencies were calculated and statistical analysis was then carried out. Comparative studies were carried out with referring to allele distribution from other populations. This study produces a database for random Duson population and hopefully will help in human identification in Malaysia. We also fid out that the genotype frequency distributions do not deviate from Hardy-Weinberg expectations.